High-Figure-of-Merit Biosensing and Enhanced Excitonic Absorption in an MoS2-Integrated Dielectric Metasurface - Bradley, Louise (My University, 2023)
Among the transitional metal dichalcogenides (TMDCs), molybdenum disulfide (MoS2) is considered an outstanding candidate for biosensing applications due to its high absorptivity and amenability to ionic current measurements. Dielectric metasurfaces have also emerged as a powerful platform for novel optical biosensing due to their low optical losses and strong near-field enhancements. Once functionalized with TMDCs, dielectric metasurfaces can also provide strong photon-exciton interactions. Here, we theoretically integrated a single layer of MoS2 into a CMOS-compatible asymmetric dielectric metasurface composed of TiO2 meta-atoms with a broken in-plane inversion symmetry on an SiO2 substrate. We numerically show that the designed MoS2-integrated metasurface can function as a high-figure-of-merit (FoM=137.5 RIU-1) van der Waals-based biosensor due to the support of quasi-bound states in the continuum. Moreover, owing to the critical coupling of the magnetic dipole resonances of the metasurface and the A exciton of the single layer of MoS2, one can achieve a 55% enhanced excitonic absorption by this two-port system. Therefore, the proposed design can function as an effective biosensor and is also practical for enhanced excitonic absorption and emission applications.
PUBLISHED
Keywords: Quasi-bound states in the continuum; Enhanced excitonic absorption; Dielectric metasurfaces; MoS2; Biosensing; Broken in-plane inversion symmetry